2021
DOI: 10.1186/s13063-020-05004-8
|View full text |Cite
|
Sign up to set email alerts
|

Managing clinical trials during COVID-19: experience from a clinical research facility

Abstract: There is a dearth of literature on best practices for managing clinical trials, and little is understood on the role of the clinical trial manager. The COVID-19 pandemic has brought this into focus, and the continuance of clinical trials worldwide has been catapulted into a state of uncertainty as countries enter lockdown to manage the spread of the virus. Participant retention is an ongoing issue in clinical trials, and the concern is that in the current pandemic environment, attrition will be an issue which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 10 publications
2
55
0
Order By: Relevance
“…Prior research has reported various strategies to ensure the continuation and/or resumption of non-COVID-19 trials during the pandemic [6,7]. As these reports have been restricted in scope to pharmacological interventions and HIC perspectives, they may have limited utility to trialists testing psychological interventions in lowresource settings where trial conduct is substantially more challenging [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has reported various strategies to ensure the continuation and/or resumption of non-COVID-19 trials during the pandemic [6,7]. As these reports have been restricted in scope to pharmacological interventions and HIC perspectives, they may have limited utility to trialists testing psychological interventions in lowresource settings where trial conduct is substantially more challenging [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Around the world, non-COVID-19 clinical trials have been suspended or halted due to COVID-19 regulations, sponsor or funder directives and operational challenges [3][4][5]. Non-COVID-19 trials permitted to continue or resume and required substantial adjustments to recruitment, intervention, data collection and trial management protocols in response to the social distancing and quarantine challenges posed by COVID-19 [6,7]. Recent systematic reviews and studies have reported that these mitigation efforts have resulted in enrolment delays and operational gaps that have negatively impacted on trial timelines and outcomes [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the midst of all the unknowns in a global pandemic, these safety decisions were often incredibly complicated. Many clinical trial populations still desperately needed treatment options; however, these same populations were often also be at higher risk for serious complications from COVID-19 infection [ 4 , 7 ].…”
Section: Clinical Trial Disruption and Opportunitymentioning
confidence: 99%
“…Testing laboratories were also operating with diminished workforces. Entirely new ways of working have been developed as organizations moved to virtual platforms [ 4 ]. The operation of the bioanalytical laboratory was disrupted.…”
Section: Clinical Trial Disruption and Opportunitymentioning
confidence: 99%